Dimensional approaches to psychiatric classification: refining the research agenda for DSM‐V: an introduction - Regier, Darrel A. (Int J Methods Psychiatr Res, 2007)
The American Psychiatric Association (APA) will publish the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM‐V), in 2012. This paper reviews the extended, multi‐faceted research planning preparations that APA has undertaken, several in collaboration with the World Health Organization and the U.S. National Institutes of Health, to assess the current state of diagnosis‐relevant research and to generate short‐ and long‐term recommendations for research needed to enrich DSM‐V and future psychiatric classifications. This research review and planning process has underscored widespread interest among nosologists in the US and globally regarding the potential benefits for research and clinical practice of incorporating a dimensional component into the existing categorical, or binary, classification system in the DSM. Toward this end, the APA and its partners convened an international conference in July 2006 to critically appraise the use of dimensional constructs in psychiatric diagnostic systems. Resultant papers appear in this issue of International Journal of Methods in Psychiatric Research and in a forthcoming monograph to be published by APA. Copyright © 2007 John Wiley & Sons, Ltd.